The Relationship between Organizational Justice and Turnover Intention: A Survey on Hospital Nurses - Mobin Sokhanvar; Edris Hasanpoor; Soodeh Hajihashemi; Edris Kakemam (Patient Safety and Quality Improvement Journal, 2016)
Introduction: High organizational justice and its factors are associated with reduced turnover intention. Therefore, in this study, we aimed to examine the relationship between organizational justice and turnover intention among hospital nurses. Materials and Methods: This descriptive, analytical study was conducted on 135 nurses working in Labafi Nejad Hospital in Tehran, Iran, 2015. The data were collected using Beugre's (1998) questionnaire of organizational justice questionnaire. To analyze the data, Pearson’s correlation and ANOVA tests were performed using SPSS, version 20. Results: Mean organizational justice and turnover intention scores were 68.85±7.67 and 47.8±12.47, respectively. Among the different types of organizational justice, the highest mean score was pertinent to interactional justice (75.24±16.68). A significant inverse correlation was observed between turnover intention and organizational justice (r=-0.36), interactional justice (r=-0.38), and procedural justice (r=-0.36), while no association was noted between turnover intention and systemic and distributive types of justice. Furthermore, there was no link between demographic variables, organizational justice, and turnover intention. Conclusion: Considering the prominent role of organizational justice in personnel’s intention to leave their job, and given high costs of recruiting and training new staff, managers should pay especial attention to promoting justice and employees’ satisfaction and enhancing stability in their organizations by reinforcing positive attitudes in the employees.